BegrensSkade II – REMEDY – Risk Reduction of Groundwork Damage: An Overview. Issue 1 (April 2021) - Langford, J; Lande, E-J; Sandene, T; Kahlstrøm, M; Nadim, F; Norén-Cosgriff, K; Piciullo, L; Ritter, S; Hauser, C; Lysdahl, A; Attari, Y; Formreide, R
Abstract: Deep excavation and foundation works in soft clays can cause large settlements, resulting in damage to neighboring buildings and structures. The costs related to these types of damage can be substantial. There is significant potential for reducing such costs if the causes are better understood and the risk is assessed during planning, design and execution. The research project "BegrensSkade II" ("REMEDY") focuses on developing guidelines for the main causes of excavation-induced damage related to installation effects, drainage and pore pressure lowering, and vibration effects. In addition, tools to support risk management and decision making in the building process are developed. The project is funded by the Norwegian Research Council with participation from a wide range of consultants, contractors, clients and research institutes in Norway. This paper provides an overview of the work carried out in BegrensSkade II and highlights some initial findings.